Long-armed hexapod nanocrystals of cesium lead bromide. Issue 27 (7th July 2020) - Li, Shangkun; Probst, Julie; Howes, Philip D.; deMello, Andrew J.
Abstract : Cesium lead bromide nanosheets undergo a slow transformation from nanosheets to long-armed hexapods, revealing the utility of extended incubation times in perovskite nanocrystal shape control. Abstract : Colloidal lead halide perovskite nanocrystals (LHP NCs) assume a variety of morphologies ( e.g. cubes, sheets, and wires). Their labile structural and surface characters allow them to undergo post-synthetic evolution of shape and crystallographic characters. Such transformations can be advantageous or deleterious, and it is therefore vital to both understand and exert control over these processes. In this study, we report novel long-armed hexapod structures of cesium lead bromide nanocrystals. These branched structures evolve from quantum-confined CsPbBr3 nanosheets to Cs4 PbBr6 hexapods over a period of 24 hours. Time-resolved optical and structural characterization reveals a post-synthesis mechanism of phase transformation, oriented attachment and branch elongation. More generally, the study reveals important processes associated with LHP NC aging and demonstrates the utility of slow reaction kinetics in obtaining complex morphologies.